The Influence of Promotions and Prices on The Decision to Purchase Facial Makeup Services at The Hellobeauty Marketplace Service - Melinda, Farah; Febriana , Rina; Siregar , Jenny Sista (Kirana Publisher (KNPub), 2024)
With the aim of increasing sales of beauty services on the HelloBeauty marketplace . Such actions have a positive impact on business, especially in the beauty industry, and can contribute to the achievement of educational goals in this field. The method used in this research is a quantitative method with analysis to determine the effect of promotion and price as independent variables in influencing purchasing decisions for facial makeup services as the dependent variable. The variables in this research are promotion and price as independent variables (X) and purchasing decisions as the dependent variable (Y). Based on the results of the research and analysis that has been carried out, promotions have a positive and significant effect on purchasing decisions for makeup services on the Hellobeauty marketplace. Price has a positive and significant effect on the decision to purchase makeup services on the Hellobeauty marketplace.Keywords: promotions, sales, marketplace, services, facial make-up